2016
DOI: 10.1016/j.drup.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in Burkholderia species

Abstract: The genus Burkholderia comprises metabolically diverse and adaptable Gram-negative bacteria, which thrive in often adversarial environments. A few members of the genus are prominent opportunistic pathogens. These include B. mallei and B. pseudomallei of the B. pseudomallei complex, which cause glanders and melioidosis, respectively. B. cenocepacia, B. multivorans, and B. vietnamiensis belong to the B. cepacia complex and affect mostly cystic fibrosis patients. Infections caused by these bacteria are difficult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
268
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 281 publications
(279 citation statements)
references
References 123 publications
(182 reference statements)
2
268
0
9
Order By: Relevance
“…A critical line of defense against antimicrobial agents in Burkholderia species is the permeability barrier of the outer membrane. Most of these species contain a modified lipopolysaccharide, which results in polymyxin resistance (13). In addition, the permeability of the major outer membrane porin channel Omp38 appears to be low for antibiotics (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A critical line of defense against antimicrobial agents in Burkholderia species is the permeability barrier of the outer membrane. Most of these species contain a modified lipopolysaccharide, which results in polymyxin resistance (13). In addition, the permeability of the major outer membrane porin channel Omp38 appears to be low for antibiotics (14).…”
mentioning
confidence: 99%
“…The presence of a large number of multidrug efflux pumps, belonging to the resistance-nodulation-cell division (RND) superfamily, also plays a major role in the intrinsic resistance to a variety of antimicrobials. It has been found that some Bcc bacteria harbor between 11 and 16 hydrophobic/amphiphile efflux 1 (HAE1)-RND pumps that are responsible for drug efflux (13).…”
mentioning
confidence: 99%
“…The two most common dangerous species are B cenocepacia and B multivorans . Both have been associated with extreme multidrug resistance, a more rapid decline in lung function and mortality after transplant …”
Section: Discussionmentioning
confidence: 99%
“…One of the most common resistance mechanism seen in Burkholderia species is related to the production of β‐lactamases, including class A β‐lactamases ( Pen A and Pen B), class C β‐lactamases (like Amp C) and class D β‐lactamases. Non β‐lactamase‐mediated resistance, like efflux pumps and reduced outer membrane permeability, also plays a role in the decreased susceptibility of Bcc species toward beta lactam antibiotics . Avibactam is a novel β‐lactamase inhibitor which contrasts the activities of Ambler class A‐serine, C‐serine β‐lactamases and some Ambler class D‐serine enzymes (OXA‐48) to restore the susceptibility to ceftazidime by preventing enzymatic hydrolysis without changing the Class B‐MBL .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation